A note on the shear modulus of a binary elastic mixture (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2001)
The Hashin-Shtrikman and Walpole bounds on the effective shear modulus of a binary elastic mixture are revisited. A simple method of derivation is given as a generalization of the approach, recently proposed by one of the authors in the absorption and scalar conductivity problems for a two-phase medium.